Isolation, Purification, and Toxicity Test of Bacillus thuringiensis from Cows Cage Soil Againts Drosophila melanogaster - Syamsul Bahri; Lalu Zulkifli; Dewa Ayu Citra Rasmi; Prapti Sedijani (Jurnal Biologi Tropis, 2021)
Bacillus thuringiensis is one of the bacteriae species that be able to kill insects. The latest research showed that the cell plasm of this bacteria contains crystalline protein with natural insectisides properties. Therefore the insecticidal effect of this species on insects which is decreasing cultivation plant production is interest to be examined. One of the insect species that are well-known causes of loss of farm production in fruit flies (Drosophila melanogaster). Therefore this research is designed to isolate, purify, and thenassess Bacillus thuringiensis toxicity against Drosophila melanogaster as animal treatment. Bacillus thuringiensis was successfully isolated from soil ofÃÂ  cows cage by using Lauria Bertani medium contain 0,25 M buffer solution Acetic, pH 6.8. The result shows that Bacillus thuringiensis isolate is a gram-positive bacteria. Position of endospore is located between the middle and the end of the cell (subterminal spore). Toxicity test was conducted by mixing 0.5 g/L, 1 g/L, 2 g/L, 4 g/L of pure Bacillus thuringiensis isolate intoÃÂ  Drosophila melanogaster medium. The treatments effect were monitored for 15 consecutive days. Toxicity test shows that the treatment has no significant effect on the treated animal mortality. This result shows that crystal-producing Bacillus thuringiensis strain isolated from cows cage soil do not have insecticidal properties for Drosophila melanogaster. It is concluded that Drosophila melanogaster is a non-target species of Bacillus thuringiensis.